Efektivitas Bimbingan Kelompok Dengan Teknik Round Robin Untuk Meningkatkan Etika Dalam Bermedia Sosial Di SMK Cut Nya’ Dien Semarang - Siti Masfufah (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2021)
Abstract: The problem raised from this research is related to ethics in social media students at SMK Cut Nya' Dien Semarang. The purpose of this study was to determine the effect of group guidance services using the round robin technique on ethics in social media for students at SMK Cut Nya' Dien Semarang. This type of research is quantitative in the form of a quasi-experimental design with a nonequivalent control group design. The population used was class X students majoring in accounting at SMK Cut Nya' Dien Semarang. The sample was taken using purposive sampling taken as many as 20 students to be used as an experimental group and a control group, the data in this study was obtained through a research instrument in the form of a Likert scale of ethics in social media. The results showed that the ethics in social media of students before and after being given treatment in the form of group guidance services with the round robin technique increased by 21.1%. The round robin technique can be used to make students brave in expressing their opinions and understanding ethics in social media. In addition, the data obtained through the T-Test test with a significant level of 5%. The sig value <0.05 was obtained so that Ha was accepted and Ho was rejected. The conclusion is that after being given treatment in the form of group guidance services with the round robin technique, there is an increase in ethics in social media for students at Cut Nya' Dien Vocational School Semarang. Based on the results of this study, suggestions that can be conveyed are to be better at making the implementation of counseling guidance services more effective, especially in group guidance services with the round robin technique to help prevent and solve problems faced by students.Key Words: group guidance, round robin, social media etiquette